2018
DOI: 10.1084/jem.20171274
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac macrophages promote diastolic dysfunction

Abstract: Hulsmans et al. show that cardiac macrophages expand in left ventricular diastolic dysfunction, a hallmark of heart failure with preserved ejection fraction (HFpEF) and cardiac aging. In HFpEF, macrophages shift toward a profibrotic subset that promotes ventricular stiffness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

18
362
0
8

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 375 publications
(388 citation statements)
references
References 53 publications
18
362
0
8
Order By: Relevance
“…The resulting increase in LV collagen content is a major contributor to the increase in passive myocardial fibre stiffness, which eventually leads to diastolic dysfunction and HFpEF. Importantly, it has been recently shown that the number of macrophages in the heart increase both in animal models and in humans with HFpEF (Hulsmans et al., ). Collectively, these data indicate that macrophages and their secreted proteins play a central role in cardiomyocyte hypertrophy and HFpEF progression (Frantz et al., ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The resulting increase in LV collagen content is a major contributor to the increase in passive myocardial fibre stiffness, which eventually leads to diastolic dysfunction and HFpEF. Importantly, it has been recently shown that the number of macrophages in the heart increase both in animal models and in humans with HFpEF (Hulsmans et al., ). Collectively, these data indicate that macrophages and their secreted proteins play a central role in cardiomyocyte hypertrophy and HFpEF progression (Frantz et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…In another study, IL‐18 mediated cardiac hypertrophy in rabbits with pressure overload (Yoshida et al., ). Moreover, recent studies in murine models of HFpEF and humans with the disease identified osteopontin as an important mediator in the interaction between macrophages and fibroblasts, where macrophages activate the proliferation of myofibroblasts and production of collagen, which then leads to fibrosis‐mediated cardiac stiffness and eventually HFpEF (Hulsmans et al., ). In addition, IL‐11 is a crucial determinant of cardiac fibrosis (Schafer et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, expression of these genes by cTM increases with age, particularly at the epicardium, suggests that cTM‐mediated ECM remodelling influences cardiac ageing . Accordingly, cTM have been found to affect diastolic function of the heart by controlling extracellular matrix deposition by fibroblasts . These evidences, as with microglia, suggest trophic roles for cTM in heart homeostasis and highlight a potential role for these resident cells in many more cardiac processes than previously anticipated.…”
Section: Trophic Functions: Influence On Tissue Homeostasismentioning
confidence: 73%
“…cTM also contribute to cardiac fibrosis, a hallmark of cardiac senescence that increases with age . cTM secrete a number of pro‐fibrotic factors such as Retnla , Ccl24 , osteopontin, and Tgf1b that may induce fibroblast proliferation and collagen deposition by both TGF‐β‐dependent and ‐independent pathways . In addition, expression of these genes by cTM increases with age, particularly at the epicardium, suggests that cTM‐mediated ECM remodelling influences cardiac ageing .…”
Section: Trophic Functions: Influence On Tissue Homeostasismentioning
confidence: 99%
See 1 more Smart Citation